Microgravity promotes differentiation and meiotic entry of postnatal mouse male germ cells. - Manuela Pellegrini (Public Library of Science (PLoS), 2010)
A critical step of spermatogenesis is the entry of mitotic spermatogonia into meiosis. Progresses on these topics are hampered by the lack of an in vitro culture system allowing mouse spermatogonia differentiation and entry into meiosis. Previous studies have shown that mouse pachytene spermatocytes cultured in simulated microgravity (SM) undergo a spontaneous meiotic progression. Here we report that mouse mitotic spermatogonia cultured under SM with a rotary cell culture system (RCCS) enter into meiosis in the absence of any added exogenous factor or contact with somatic cells. We found that isolated Kit-positive spermatogonia under the RCCS condition enter into the prophase of the first meiotic division (leptotene stage), as monitored by chromosomal organization of the synaptonemal complex 3 protein (Scp3) and up-regulation of several pro-meiotic genes. SM was found to activate the phosphatidyl inositol 3 kinase (PI3K) pathway and to induce in Kit-positive spermatogonia the last round of DNA replication, typical of the preleptotene stage. A PI3K inhibitor abolished Scp3 induction and meiotic entry stimulated by RCCS conditions. A positive effect of SM on germ cell differentiation was also observed in undifferentiated (Kit-negative) spermatogonia, in which RCCS conditions stimulate the expression of Kit and Stra8. In conclusion, SM is an artificial environmental condition which promotes postnatal male germ cell differentiation and might provide a tool to study the molecular mechanisms underlying the switch from mitosis to meiosis in mammals.